Modeling and simulation of single-electron transistors - Lee, Jia Yen; Mat Isa, Ahmad Radzi; Ahmad Dasuki, Karsono (Ibnu Sina Institute for Fundamental Science Studies, 2005)
Single-electron transistor (SET) can offer lower power consumption and faster operating speed in the era of nanotechnology. It operates in single electronics regime where only one electron can tunnel from source to drain via island. Thus single electron tunneling is the phenomena that describe the principle of SET. Owing to the stochastic nature of the tunneling event, a tunneling electron is considered as a discrete charge. To simulate the SET, Monte Carlo method is used due to its reasonable accuracy in the single electronics simulation. A model is described and used to study the electronic properties of SET. Monte Carlo method follows the tunneling path of a representative number of electrons and it can gives a clear picture of the inner work of the single electron circuits.